Deliberations of the Strategic Advisory Group of Experts on Immunization on the use of CYD-TDV dengue vaccine. Issue 1 (January 2019) - Wilder-Smith, Annelies; Hombach, Joachim; Ferguson, Neil; Selgelid, Michael; O'Brien, Kate; Vannice, Kirsten; Barrett, Alan; Ferdinand, Elizabeth; Flasche, Stefan; Guzman, Maria; Novaes, Hillegonde Maria; Ng, Lee-Ching; et al.
Summary: The Strategic Advisory Group of Experts (SAGE) on Immunization advises WHO on global policies for vaccines. In April, 2016, SAGE issued recommendations on the use of the first licenced dengue vaccine, CYD-TDV. In November, 2017, a retrospective analysis of clinical trial data, stratifying participants according to their dengue serostatus before the first vaccine dose, showed that although in high seroprevalence settings the vaccine provides overall population benefit, there was an excess risk of severe dengue in seronegative vaccinees. SAGE's working group on dengue vaccines met to discuss the new data and mainly considered two vaccination strategies: vaccination of populations with dengue seroprevalence rates above 80% or screening of individuals before vaccination, and vaccinating only seropositive individuals. We report on the deliberations that informed the recommendation of the pre-vaccination screening strategy, in April, 2018. Important research and implementation questions remain for CYD-TDV, including the development of a highly sensitive and specific rapid diagnostic test to determine serostatus, simplified immunisation schedules, and assessment of the need for booster doses.